Study of Entrepreneurial Intention and Its Influencing Factors among Researchers - A Case Study of the University of Boumerdes - Amina Meziane (المجلة الدولية للأداء الاقتصادي, 2023)
The aim of this study is to identify the presence of entrepreneurial intention among Algerian researchers for creating academic spin-offs. We relied on a questionnaire administered to 88 researchers from the University of Boumerdes. The findings led to the conclusion that researchers show limited interest in starting a business. Furthermore, desirability and feasibility are the primary factors influencing this inclination. To facilitate the establishment of such enterprises, a comprehensive framework enveloping legislative, cultural, and financing elements is essential to improve the capacity of universities in forming spin-off companies.